2021
DOI: 10.1007/s00167-021-06681-x
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in scapular dyskinesis after rotator cuff repair and subacromial decompression

Abstract: PurposeTo investigate the incidence of scapular dyskinesis (SD) in patients with rotator cuff tears using pre‐ and postoperative 3D computed tomography, analyze the changes in scapular kinematics that occur after arthroscopic rotator cuff repair, and identify the contributing clinical factors. MethodsThirty‐five patients (mean age, 62.5 ± 8.4 years) were included. Four scapular angles (upward rotation, internal rotation, protraction, and posterior tilt) were measured. The patients were categorized into three p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…On the other hand, there was no statistically significant difference between early and late groups in scapular upward rotation at 45⁰, 90⁰ and 135⁰ ROM of shoulder abduction. Ueda and his colleagues (2019) observed that scapular movement did not recover after rehabilitation to the same level as that of the healthy controls (22). In contrast to this observation, another study reported that small and large RCT patients had higher scapular upward rotation during arm elevations compared to healthy controls (23).…”
Section: Discussionmentioning
confidence: 96%
“…On the other hand, there was no statistically significant difference between early and late groups in scapular upward rotation at 45⁰, 90⁰ and 135⁰ ROM of shoulder abduction. Ueda and his colleagues (2019) observed that scapular movement did not recover after rehabilitation to the same level as that of the healthy controls (22). In contrast to this observation, another study reported that small and large RCT patients had higher scapular upward rotation during arm elevations compared to healthy controls (23).…”
Section: Discussionmentioning
confidence: 96%
“…Scapular dyskinesis is a common condition in a variety of shoulder disorders, including rotator cuff tears [1][2][3][4][5], with the medio-lateral and anterior-posterior scapular rotations most commonly affected [6]. The evaluation and treatment of scapular dyskinesis are challenging; in particular, finding accurate and repeatable measures to define "how much" scapular movement is dyskinetic and if it is a cause or effect of the rotator cuff tear is objectively difficult [7,8].…”
Section: Introductionmentioning
confidence: 99%